Factores académicos incidentes en el desempeño de los estudiantes de asignaturas virtuales, CUC (2015)
This research supports the academic process of virtual classrooms in the CUC, this type of study is considered nowadays a trend because of the space-time, method, and flexible techniques consolidation. This way the scholar process gets sharpened up, and it makes possible to researchers analyzing how academic elements have an impact on the student’s virtual classroom performance. We have planned to present qualitative results based on an interpretative perspective while gathering up documentary, quoting classified authors, surveying a segment of 90 students from a 2,144 community each of them signed up in the virtual classrooms available within the CUC. At the end they are shown as results of how some academic elements are decisive in the student’s performance. This investigation was mainly aimed to contribute in the improvement on the students’ performance who has signed up in virtual classroom as well.